Surface-modified lithium cobalt oxide material, preparation method thereof and application of surface-modified lithium cobalt oxide material in high-voltage lithium battery
By coating the lithium cobalt oxide material with fluoride phosphate to form a surface modified layer, the problem of electrochemical performance decay of lithium cobalt oxide positive electrode material under high voltage fast charging conditions is solved, the structural stability and conductivity of the material are improved, and the energy density and power density of lithium-ion batteries are improved.
Patent Information
- Application Number
- CN202311181057.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-09-13
AI Technical Summary
The electrochemical performance of lithium cobalt oxide cathode material has severely declined under high voltage fast charging conditions, resulting in structural instability and material polarization, affecting the energy density and power density of lithium-ion batteries.
The lithium cobalt oxide material is coated by fluoride phosphate to form a surface modified layer to enhance the structural stability and electrical conductivity of the material. The method includes mixing lithium cobalt oxide with raw materials such as fluoride phosphate in a specific proportion, and annealing at high temperature to form a fluoride lithium cobalt oxide positive electrode material.
It significantly improves the fast charging performance and cycle stability of lithium cobalt oxide positive electrode material at high voltage, enhances the ionic and electronic conductivity of the material, and extends the cycle life of the battery.
Smart Images

Figure CN119627059A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a surface-modified lithium cobalt oxide material, a preparation method thereof, and an application thereof in a high-voltage lithium battery. Background Art
[0002] Lithium cobalt oxide cathode materials have the advantages of high compaction density, high volume energy density and long cycle life, and they play an important role in the portable electronic terminal equipment market such as computers, communications and consumer products. As electronic products develop towards diversification, thinness, high performance and intelligence, the battery market is in urgent need of small energy storage devices with high energy density and high power density.
[0003] Improving the fast charging performance and charging cut-off voltage of lithium cobalt oxide positive electrodes is an important way to improve the energy density and power density of lithium-ion batteries. However, with the increase of fast charging rate and charging cut-off voltage, the electrochemical performance of lithium cobalt oxide positive electrodes seriously declines. This is mainly because the side reactions at the interface between the positive electrode material and the electrolyte are intensified under high charging cut-off voltage, and the high degree of delithiation leads to irreversible phase change. The polarization of the material under fast charging leads to the intensification of surface side reactions and the production of irreversible phase change, which in turn accelerates the decline of the electrochemical performance of the lithium cobalt oxide positive electrode material.
[0004] Therefore, improving structural stability and reducing material polarization are the technical key points that need to be overcome to increase the fast charging performance and charging cut-off voltage of lithium cobalt oxide positive electrodes, and are also an important direction for the development of new advanced lithium-ion battery positive electrode materials in recent years. Summary of the invention
[0005] In view of this, the present invention provides a surface-modified lithium cobalt oxide material, a preparation method thereof and an application in a high-voltage lithium battery, the main purpose of which is to solve the technical problem that the electrochemical performance of high-voltage fast-charging lithium cobalt oxide positive electrode materials needs to be improved.
[0006] On the one hand, the present invention provides a surface-modified lithium cobalt oxide material, wherein the surface-modified lithium cobalt oxide material is lithium cobalt oxide modified by fluorinated phosphate, and the fluorinated phosphate is coated on the surface of the lithium cobalt oxide material.
[0007] Optionally, the molar number of phosphorus atoms in the fluorinated phosphate of the coating layer is 0.02% to 10% of the molar number of cobalt atoms in the lithium cobaltate.
[0008] Optionally, the molar number of phosphorus atoms in the coating layer fluorinated phosphate is 0.02%, 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 0.8%, 1.0%, 1.3%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.8%, 3%, 3.3%, 3.5%, 3.8%, 4%, 4.3%, 4.5%, 4.8%, 5%, 5.3%, 5.5%, 5.8%, 6%, 6.3%, 6.5%, 6.8%, 7%, 7.3%, 7.5%, 7.8%, 8%, 8.3%, 8.5%, 8.8%, 9%, 9.3%, 9.5%, 9.8%, 10% of the molar number of cobalt atoms in the lithium cobaltate, or a range value between any two of them.
[0009] Optionally, the surface-modified lithium cobalt oxide material has a reversible specific capacity of 200 to 225 mAh / g at a rate of 0.2C in a voltage range of 3.0 to 4.6 V, and a reversible specific capacity of 150 to 190 mAh / g at a rate of 10C.
[0010] Optionally, the reversible specific capacity of the surface-modified lithium cobalt oxide material at a rate of 0.2C is selected from any value of 200, 205, 210, 215, 220, 225 mAh / g or any range between two values.
[0011] Optionally, the reversible specific capacity of the surface-modified lithium cobalt oxide material at a rate of 10 C is any value of 150, 155, 160, 165, 170, 175, 180, 185, 190 mAh / g or a range between any two of them.
[0012] In a second aspect, the present invention provides a method for preparing the surface-modified lithium cobalt oxide material, the preparation method comprising the following steps:
[0013] S1: Obtain lithium cobalt oxide;
[0014] S2: mixing the raw materials including the lithium cobalt oxide, lithium source, fluorine source, phosphorus source and transition metal salt described in step S1 to obtain a precursor dry material;
[0015] S3: The precursor dry material in step S2 is heated for I and kept warm for I in an inert atmosphere to obtain a lithium cobalt oxide positive electrode material with a surface modified by fluorinated cobalt phosphate.
[0016] Optionally, in step S2, the atomic molar ratio of the lithium cobalt oxide, the lithium source, the fluorine source, the phosphorus source and the transition metal salt is (1-2x): 1x: 1x: 1x: 1x, 0.0002≤x≤0.1;
[0017] The atomic mole number of the lithium cobalt oxide is calculated as the atomic mole number of cobalt.
[0018] The atomic mole number of the lithium source is calculated as the mole number of lithium atoms,
[0019] The atomic mole number of the fluorine source is calculated as the mole number of fluorine atoms,
[0020] The atomic mole number of the transition metal salt is calculated based on the atomic mole number of the metal corresponding to it.
[0021] In the present invention, the “-” in the above “(1-2x)” means 1 minus 2x.
[0022] In the present invention, when the transition metal salt is a plurality of composite metal salts, the atomic mole number thereof is the total mole number of metal atoms in the plurality of metal salts.
[0023] Optionally, x in step S2 is selected from any value among 0.0002, 0.0005, 0.0008, 0.0010, 0.003, 0.005, 0.008, 0.010, 0.020, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or any range between two of them.
[0024] Optionally, in step S3, the temperature of the heating I is 600-1000° C., and the time of the insulation I is 2-6 hours.
[0025] Optionally, the inert atmosphere includes an argon medium.
[0026] Optionally, the temperature of the heating I is selected from any value of 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C or any range therebetween.
[0027] Optionally, the insulation time I is selected from any value among 2, 3, 4, 5, 6 hours or any range value between two of them.
[0028] Optionally, in step S2, the lithium source is selected from at least one of lithium carbonate, lithium chloride, lithium hydroxide and lithium fluoride.
[0029] Optionally, in step S2, the fluorine source is selected from lithium fluoride and / or ammonium fluoride.
[0030] Optionally, in step S2, the phosphorus source is at least one of phytic acid, phosphoric acid, lithium dihydrogen phosphate and ammonium phosphate.
[0031] Optionally, in step S2, the transition metal salt is selected from at least one of cobalt acetate or nitrate, copper acetate or nitrate, lanthanum acetate or nitrate, and aluminum acetate or nitrate.
[0032] Optionally, in step S1, the lithium cobalt oxide is a product of mixing cobalt trioxide and lithium carbonate, heating II in an air medium, and keeping II;
[0033] The atomic molar ratio of the cobalt oxide to the lithium carbonate is 1:1 to 1.1; the temperature of the heating II is 600 to 1000° C.; the time of the heat preservation II is 2 to 6 hours;
[0034] Wherein, the atomic mole number of the cobalt tetroxide is calculated as the atomic mole number of cobalt.
[0035] The atomic mole number of the lithium carbonate is calculated as the atomic mole number of lithium.
[0036] Optionally, the temperature of the heating II is selected from any value of 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C or any range therebetween.
[0037] Optionally, the insulation II time is selected from any value among 2, 3, 4, 5, 6 hours or any range value between two of them.
[0038] Optionally, the atomic molar ratio of the cobalt trioxide to the lithium carbonate is selected from any value of 1:1, 1:1.05, 1:1.1, or any range value between the two.
[0039] Optionally, the cobalt oxide includes flaky nano cobalt oxide powder and spherical nano cobalt oxide powder.
[0040] Optionally, the preparation method of the flaky nano-cobalt oxide powder includes: heating cobalt salt and ammonia water at 60-100° C., keeping warm for 1-24 hours, and obtaining nano-cobalt hydroxide powder after centrifugal drying; heating the nano-cobalt hydroxide powder in an air medium for III and keeping warm for III to obtain a product; wherein the heating temperature for III is 600-1000° C., and the keeping time for III is 2-6 hours.
[0041] Optionally, the temperature of the heating III is selected from any value of 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C or any range therebetween.
[0042] Optionally, the insulation III time is selected from any value among 2, 3, 4, 5, 6 hours or any range value between two of them.
[0043] Optionally, the preparation method of the spherical nano-cobalt oxide powder includes: hydrothermally reacting cobalt salt and sodium acetate under closed conditions at 100-250° C. for 5-48 hours, separating and drying the reaction liquid to obtain the product, and the drying temperature is 40-100° C.
[0044] Optionally, the cobalt salt used in the preparation process of cobalt tetroxide is selected from at least one of cobalt acetate, cobalt sulfate, cobalt nitrate and cobalt chloride.
[0045] The cobalt tetraoxide in the present invention can also be obtained from the prior art.
[0046] Optionally, in step S3, the heating rate of heating I is 5 to 20°C / min; the heating rate of heating II is 5 to 20°C / min; and the heating rate of heating III is 5 to 20°C / min.
[0047] The present invention provides a specific method for preparing a surface-modified high-voltage fast-charge lithium cobalt oxide positive electrode material, the method comprising the following steps:
[0048] S1. Preparation of spherical nano-cobalt oxide powder:
[0049] Weigh 10-100 mg sodium acetate, 50-1000 mg polyvinyl pyrrolidone, and 100-1000 mg cobalt nitrate hexahydrate and gradually dissolve them in 40-80 mL deionized water. Stir evenly for 0.5-3 h at a stirring speed of 100-1000 rpm;
[0050] Transfer the above solution into a 100 ml hydrothermal reactor and react for 5-48 hours at a temperature of 100-250°C.
[0051] The reaction solution is centrifuged and washed with deionized water for 2-3 times at a centrifugal speed of 4000-10000 r / min. The separated product is placed in a 40-100° C. oven for drying to obtain spherical nano-cobalt trioxide powder.
[0052] S2. Preparation of flaky nano-cobalt oxide powder:
[0053] Weigh 1-20g of cobalt nitrate hexahydrate and disperse it in 0.5-1.0L of deionized water. Heat in an oil bath to 60-100°C.
[0054] Add 5-30 mL of 25% ammonia water to the above solution, keep warm and stir at a stirring speed of 100-1000 rpm for 1-24 hours;
[0055] The reaction product is centrifugally washed, ultrasonically dispersed and freeze-dried to obtain nanometer cobalt hydroxide powder, and the centrifugal speed is 4000-10000r / min.
[0056] The cobalt hydroxide powder is placed in a muffle furnace, heated and kept warm in air medium, with a heating rate of 5-20°C / min, a temperature of 600-1000°C, and a holding time of 2-6h. After natural cooling, nanometer cobalt trioxide powder is obtained.
[0057] S3, Fluorinated phosphate surface modified lithium cobalt oxide positive electrode material:
[0058] Weigh the above cobalt oxide powder (optionally S1 or S2) at an atomic molar ratio of 1:1.05, mix and grind to obtain a precursor dry material. Place the above dry material in a muffle furnace, heat and keep it warm in air medium, 5-20℃ / min, temperature is 600-1000℃, and the insulation time is 2-6h.
[0059] According to the atomic molar ratio of 1-2x:x:x:x:x, where: 0.02%≤x≤10% (the % represents a numerical percentage, such as 0.02% is 0.0002, and 10% is 0.1), weigh the lithium cobalt oxide powder, lithium source, fluorine source, phosphorus source, and transition metal salt prepared above, mix and grind to obtain a precursor dry material.
[0060] The above-mentioned dry precursor material is placed in a tube furnace, heated and kept warm in an argon medium, 5-20°C / min, the temperature is 600-1000°C, and the holding time is 2-6h. After the heating process is completed, the product is taken out to obtain a fluorinated phosphate lithium cobalt oxide positive electrode material.
[0061] Optionally, the polyvinyl pyrrolidone in S1 is one or more of PVP-K12, PVP-K15, PVP-K17, PVP-K25, PVP-K30, PVP-K60, and PVP-K90.
[0062] In a third aspect, the present invention provides a lithium cobalt oxide positive electrode component, comprising a conductive substrate and a slurry coated on the surface of the conductive substrate; the raw material of the slurry comprises the above-mentioned surface-modified lithium cobalt oxide material.
[0063] Optionally, the preparation method of the lithium cobalt oxide positive electrode component is as follows: the lithium cobalt oxide material is mixed with conductive carbon black and polyvinylidene fluoride adhesive in a mass ratio of (6-10):1:1 and ground, and then an appropriate amount of solvent is added to form a slurry; the slurry is evenly scraped on a carbon-coated aluminum foil, and the positive electrode sheet is obtained after drying.
[0064] In a fourth aspect, the present invention provides a high-voltage fast-charging lithium-ion battery, comprising a positive electrode component, a negative electrode component, a separator, and an electrolyte; the positive electrode component is the above-mentioned lithium cobalt oxide positive electrode component.
[0065] Optionally, the negative electrode is a metal lithium sheet, the separator is a Celgard2400 membrane, the electrolyte is a LB-372 high-voltage electrolyte; and the battery is a CR2016 button battery.
[0066] Optionally, the battery is a CR2016 button battery.
[0067] In a fifth aspect, the present invention provides the use of the above-mentioned surface-modified lithium cobalt oxide material in a high-voltage ultra-fast charging lithium cobalt oxide battery.
[0068] Compared with the prior art, the present invention has the following beneficial effects:
[0069] 1) The fast-charging high-voltage lithium cobalt oxide positive electrode material prepared by the present invention is modified by surface coating with fluorinated phosphate. By optimizing the raw materials, doping content and preparation process, not only the reversibility of the bulk crystal structure of the material and the structural stability of the surface under high voltage are improved, but also the ionic conductivity and electronic conductivity of the material are improved, thereby achieving the improvement of the high-voltage ultra-fast charging performance and cycle stability of the lithium cobalt oxide positive electrode material.
[0070] 2) The preparation method provided by the present invention has good controllability, is simple and easy to operate, and is suitable for expanding production and realizing industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 This is a scanning electron microscope image of the fluorinated phosphate surface-modified lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention;
[0072] Figure 2 This is a scanning electron microscope image of the unmodified spherical lithium cobalt oxide positive electrode material prepared in Comparative Example 1 of the present invention;
[0073] Figure 3 This is a scanning electron microscope image of the unmodified flaky lithium cobalt oxide positive electrode material prepared in Comparative Example 2 of the present invention;
[0074] Figure 4 The rate performance test of the surface-modified lithium cobalt oxide positive electrode material of lithium lanthanum fluoride phosphate of Example 1 of the present invention and the unmodified lithium cobalt oxide positive electrode material of Comparative Example 1 at a constant temperature of 20° C. in a voltage range of 3.0-4.6 V;
[0075] Figure 5 The charge and discharge curves of the surface-modified lithium cobalt oxide positive electrode material of lithium lanthanum phosphate fluoride of Example 1 of the present invention at different current densities in the voltage range of 3.0-4.6V at a constant temperature of 20°C;
[0076] Figure 6 The rate performance test of the surface-modified lithium cobalt oxide positive electrode material of lithium lanthanum phosphate fluoride of Example 2 of the present invention and the unmodified lithium cobalt oxide positive electrode material of Comparative Example 2 at a constant temperature of 20° C. in a voltage range of 3.0-4.5 V;
[0077] Figure 7 The charge and discharge curves of the surface-modified lithium cobalt oxide positive electrode material of lithium lanthanum phosphate fluoride of Example 2 of the present invention at different current densities in the voltage range of 3.0-4.5V at a constant temperature of 20°C. DETAILED DESCRIPTION
[0078] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.
[0079] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.
[0080] Unless otherwise specified, the analysis methods in the examples all adopt conventional settings and conventional analysis methods of instruments or equipment.
[0081] Example 1 (Fluorinated Phosphate Coated Lithium Cobalt Oxide Material)
[0082] Weigh 10 mg of sodium acetate, 50 mg of polyvinyl pyrrolidone, and 100 mg of cobalt nitrate hexahydrate and gradually dissolve them in 40 mL of deionized water. Stir evenly for 0.5 h at a stirring speed of 200 rpm; transfer the above solution to a 100 ml hydrothermal reactor and react for 12 h at a temperature of 180 °C.
[0083] The reaction solution was centrifuged and washed twice with deionized water at a centrifugal speed of 6000 r / min. The separated product was placed in an oven at 60° C. and dried to obtain spherical nano-cobalt trioxide powder.
[0084] The above cobalt trioxide powder and lithium carbonate were weighed according to the molar ratio of cobalt atoms to lithium atoms of 1:1.05, mixed and ground to obtain a precursor dry material. The above dry material was placed in a muffle furnace, heated and kept warm in an air medium at 5°C / min, the temperature was 700°C, and the holding time was 3h to obtain lithium cobalt oxide powder.
[0085] The lithium cobalt oxide powder, lithium carbonate, lithium fluoride, lithium dihydrogen phosphate, and lanthanum nitrate hexahydrate prepared above are weighed in sequence according to the molar ratio of cobalt atoms, lithium atoms, fluorine atoms, phosphorus atoms, and lanthanum atoms of 0.98:0.01:0.01:0.01:0.01 (i.e., 98:1:1:1:1), mixed and ground to obtain a precursor dry material.
[0086] The above-mentioned precursor dry material is placed in a tube furnace, heated and kept warm in an argon medium, 5°C / min, the temperature is 800°C, and the holding time is 2h. After the heating process is completed, the product is taken out to obtain a fluorinated phosphate lithium cobalt oxide positive electrode material; Figure 1 shown.
[0087] Example 2 (Fluorinated Phosphate Coated Lithium Cobalt Oxide Material)
[0088] Weigh 20g polyvinyl pyrrolidone and 5g cobalt nitrate hexahydrate and disperse them in 1.0L deionized water, and heat them in an oil bath to 80°C. Add 15mL of 25% ammonia water to the above solution, keep warm and stir at a stirring speed of 400rmp for 1h. Wash the above reaction product by centrifugation, ultrasonically disperse and freeze-dry to obtain flaky nano cobalt hydroxide powder.
[0089] The flaky nano cobalt hydroxide powder is placed in a muffle furnace and heated in an air medium at a heating rate of 5°C / min, a temperature of 450°C, and a holding time of 2 hours. After the temperature is naturally lowered, nano cobalt trioxide powder is obtained.
[0090] The above cobalt trioxide powder and lithium carbonate were weighed according to the molar ratio of cobalt atoms to lithium atoms of 1:1.05, mixed and ground to obtain a precursor dry material. The above dry material was placed in a muffle furnace, heated and kept warm in an air medium at 5°C / min, the temperature was 700°C, and the holding time was 3h to obtain lithium cobalt oxide powder.
[0091] The lithium cobalt oxide powder, lithium carbonate, lithium fluoride, lithium dihydrogen phosphate, and lanthanum nitrate hexahydrate prepared above are weighed in sequence according to the molar ratio of cobalt atoms, lithium atoms, fluorine atoms, phosphorus atoms, and lanthanum atoms of 0.9:0.05:0.05:0.05:0.05 (i.e., 90:5:5:5:5), mixed and ground to obtain a precursor dry material.
[0092] The above-mentioned dry precursor material is placed in a tube furnace, heated and kept warm in an argon medium, 5°C / min, the temperature is 800°C, and the holding time is 2h. After the heating process is completed, the product is taken out to obtain a fluorinated phosphate lithium cobalt oxide positive electrode material.
[0093] Example 3 (Fluorinated Phosphate Coated Lithium Cobalt Oxide Material)
[0094] Weigh 10 mg of sodium acetate, 50 mg of polyvinyl pyrrolidone, and 100 mg of cobalt nitrate hexahydrate and gradually dissolve them in 40 mL of deionized water. Stir evenly for 0.5 h at a stirring speed of 200 rpm; transfer the above solution to a 100 ml hydrothermal reactor and react for 12 h at a temperature of 180 °C.
[0095] The reaction solution was centrifuged and washed twice with deionized water at a centrifugal speed of 6000 r / min. The separated product was placed in an oven at 60° C. and dried to obtain spherical nano-cobalt trioxide powder.
[0096] The above cobalt trioxide powder and lithium carbonate were weighed according to the molar ratio of cobalt atoms to lithium atoms of 1:1.05, mixed and ground to obtain a precursor dry material. The above dry material was placed in a muffle furnace, heated and kept warm in an air medium at 5°C / min, the temperature was 800°C, and the holding time was 3h to obtain lithium cobalt oxide powder.
[0097] The lithium cobalt oxide powder, lithium carbonate, lithium fluoride, lithium dihydrogen phosphate, and copper nitrate hexahydrate prepared above are weighed in sequence according to the molar ratio of cobalt atoms, lithium atoms, fluorine atoms, phosphorus atoms, and copper atoms of 0.98:0.01:0.01:0.01:0.01 (i.e., 98:1:1:1:1), mixed and ground to obtain a precursor dry material.
[0098] The above-mentioned dry precursor material is placed in a tube furnace and heated in an argon medium at a temperature of 700°C for 2 hours at a rate of 5°C / min. After the heating process is completed, the product is taken out to obtain a fluorinated phosphate lithium cobalt oxide positive electrode material.
[0099] Example 4 (Fluorinated Phosphate Coated Lithium Cobalt Oxide Material)
[0100] Weigh 20g polyvinyl pyrrolidone and 5g cobalt nitrate hexahydrate and disperse them in 1.0L deionized water, and heat them in an oil bath to 80°C. Add 15mL of 25% ammonia water to the above solution, keep warm and stir at a stirring speed of 400rmp for 1h. Wash the above reaction product by centrifugation, ultrasonically disperse and freeze-dry to obtain nano cobalt hydroxide powder.
[0101] The cobalt hydroxide powder is placed in a muffle furnace and heated in an air medium at a heating rate of 5°C / min, a temperature of 450°C, and a holding time of 2 hours. After the temperature is naturally lowered, nano-cobalt trioxide powder is obtained.
[0102] The above cobalt trioxide powder and lithium carbonate were weighed according to the molar ratio of cobalt atoms to lithium atoms of 1:1.05, mixed and ground to obtain a precursor dry material. The above dry material was placed in a muffle furnace, heated and kept warm in an air medium at 5°C / min, the temperature was 900°C, and the holding time was 3h to obtain lithium cobalt oxide powder.
[0103] The lithium cobalt oxide powder, lithium carbonate, lithium fluoride, lithium dihydrogen phosphate, and aluminum nitrate prepared above are weighed in sequence according to the molar ratio of cobalt atoms, lithium atoms, fluorine atoms, phosphorus atoms, and aluminum atoms of 0.98:0.01:0.01:0.01:0.01 (i.e., 98:1:1:1:1), mixed and ground to obtain a precursor dry material.
[0104] The above-mentioned dry precursor material is placed in a tube furnace, heated and kept warm in an argon medium, 5°C / min, the temperature is 1000°C, and the holding time is 2h. After the heating process is completed, the product is taken out to obtain a fluorinated phosphate lithium cobalt oxide positive electrode material.
[0105] Comparative Example 1 (unmodified lithium cobalt oxide material)
[0106] Weigh 10 mg of sodium acetate, 50 mg of polyvinyl pyrrolidone, and 100 mg of cobalt nitrate hexahydrate and gradually dissolve them in 40 mL of deionized water. Stir evenly for 0.5 h at a stirring speed of 200 rmp; transfer the above solution to a 100 ml hydrothermal reactor and react for 12 h at a temperature of 180 ° C. Take the above reaction solution, centrifuge and wash it twice with deionized water at a centrifugal speed of 6000 r / min. Dry the separated product in a 60 ° C oven to obtain spherical nano-cobalt oxide powder.
[0107] The above cobalt oxide powder and lithium carbonate were weighed according to the molar ratio of cobalt atoms to lithium atoms of 1:1.05, mixed and ground to obtain a precursor dry material. The above dry material was placed in a muffle furnace and heated in an air medium at 5°C / min, the temperature was 700°C, and the insulation time was 3h to obtain a spherical lithium cobalt oxide positive electrode material ( Figure 2 ).
[0108] Comparative Example 2 (Unmodified LiCoO2 Material)
[0109] Weigh 20g polyvinyl pyrrolidone and 5g cobalt nitrate hexahydrate and disperse them in 1.0L deionized water, and heat them in an oil bath to 80°C. Add 15mL of 25% ammonia water to the above solution, keep warm and stir at a stirring speed of 400rmp for 1h. Wash the above reaction product by centrifugation, ultrasonically disperse and freeze-dry to obtain nano cobalt hydroxide powder.
[0110] The cobalt hydroxide powder is placed in a muffle furnace and heated in an air medium at a heating rate of 5°C / min, a temperature of 450°C, and a holding time of 2 hours. After the temperature is naturally lowered, nano-cobalt trioxide powder is obtained.
[0111] According to the molar ratio of cobalt atoms to lithium atoms of 1:1.05, cobalt trioxide and lithium carbonate were weighed, mixed and ground to obtain a precursor dry material. The precursor dry material was placed in a muffle furnace and heated and kept warm in an air medium at 5°C / min, the temperature was 800°C, and the holding time was 3h. After the heating process was completed, the product was taken out and quenched in air to obtain a flaky lithium cobalt oxide positive electrode material ( Figure 3 ).
[0112] Example 5 (lithium ion battery)
[0113] The lithium cobalt oxide positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were weighed with conductive carbon black and polyvinylidene fluoride binder at a mass ratio of 8:1:1, mixed and ground, and then an appropriate amount of N-methylpyrrolidone was added dropwise, and grinding was continued until a uniform slurry was formed. The slurry was evenly scraped on the carbon-coated aluminum foil and transferred to a vacuum oven at 100°C. After being completely dried, the aluminum foil was cut into positive electrode sheets with a diameter of 12 mm for standby use, and 6 different positive electrode sheets were obtained.
[0114] Using metallic lithium sheet as negative electrode, Celgard2400 membrane as separator, and LB-372 high-voltage electrolyte provided by Duoduo Reagent Co., Ltd., CR2016 button cells were assembled in a glove box protected by argon atmosphere to obtain 6 different batteries.
[0115] The evaluation method of the electrochemical performance of the lithium cobalt oxide positive electrode material of the present invention is as follows:
[0116] The above six batteries were placed in a constant temperature box at 28°C and tested for rate and cycle charge and discharge in the voltage window of 3.0-4.6V. Figure 4 The corresponding charge and discharge curves at different rates are shown in Figure 5 shown.
[0117] The potassium / phosphorus / fluorine surface-doped modified lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention has a reversible specific capacity of 212.2 mAh / g at a rate of 0.2C; and a reversible specific capacity of 168.7 mAh / g at a rate of 10C.
[0118] The unmodified lithium cobalt oxide positive electrode material prepared in Comparative Example 1 has a reversible specific capacity of 205.3 mAh / g at 0.2C and a reversible specific capacity of 132 mAh / g at 10C.
[0119] By comparison, it can be seen that the reversible specific capacity of the positive electrode material prepared in Comparative Example 1 is significantly lower than that of the potassium / phosphorus / fluorine surface doped and modified lithium cobalt oxide positive electrode material prepared in the present invention. The above results show that the present invention can effectively improve the rate performance and reversible specific capacity of the material by surface modification of the lithium cobalt oxide positive electrode material.
[0120] The present invention firstly adopts a solid phase method to prepare nano lithium cobalt oxide powder, and then on this basis, the nano lithium cobalt oxide powder, a lithium source, a fluorine source, a phosphorus source, and a transition metal salt are uniformly mixed according to a certain atomic ratio and subjected to high temperature annealing treatment to obtain a fluorinated phosphate-coated lithium cobalt oxide positive electrode material.
[0121] The present invention greatly improves the bulk structural stability of lithium cobalt oxide positive electrode materials, inhibits the side reaction of the particle and electrolyte interface under high voltage, and greatly improves the ionic conductivity and electronic conductivity of lithium cobalt oxide positive electrode materials, thereby improving the high voltage fast charging performance and high voltage cycle stability of lithium cobalt oxide positive electrode materials. The preparation method provided by the present invention has good controllability, is simple and easy to operate, and is suitable for expanding production and realizing industrialization.
[0122] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A surface-modified lithium cobalt oxide material, characterized in that: The surface-modified lithium cobalt oxide material is lithium cobalt oxide modified by fluorinated phosphate, and the fluorinated phosphate is coated on the surface of the lithium cobalt oxide material.
2. The surface-modified lithium cobalt oxide material according to claim 1, characterized in that: The molar number of phosphorus atoms in the fluorinated phosphate of the coating layer is 0.02% to 10% of the molar number of cobalt atoms in the lithium cobalt oxide.
3. The surface-modified lithium cobalt oxide material according to claim 1, characterized in that: The surface-modified lithium cobalt oxide material has a reversible specific capacity of 200 to 225 mAh / g at a rate of 0.2C in a voltage range of 3.0 to 4.6 V, and a reversible specific capacity of 150 to 190 mAh / g at a rate of 10C.
4. The method for preparing the surface-modified lithium cobalt oxide material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: S1: Obtain lithium cobalt oxide; S2: mixing the raw materials including the lithium cobalt oxide, lithium source, fluorine source, phosphorus source and transition metal salt described in step S1 to obtain a precursor dry material; S3: The precursor dry material in step S2 is heated for I and kept warm for I in an inert atmosphere to obtain a lithium cobalt oxide material with a fluorinated phosphate surface modified.
5. The method for preparing the surface-modified lithium cobalt oxide material according to claim 4, characterized in that: In step S2, the atomic molar ratio of the lithium cobalt oxide, the lithium source, the fluorine source, the phosphorus source and the transition metal salt is (1-2x): 1x: 1x: 1x: 1x, 0.0002≤x≤0.1; The atomic mole number of the lithium cobalt oxide is calculated as the atomic mole number of cobalt. The atomic mole number of the lithium source is calculated as the mole number of lithium atoms, The atomic mole number of the fluorine source is calculated as the mole number of fluorine atoms, The atomic mole number of the transition metal salt is calculated by the atomic mole number of the metal corresponding to it; Preferably, in step S3, the temperature of the heating I is 600-1000° C., the time of the heat preservation I is 2-6 hours; the inert atmosphere includes an argon medium; Preferably, in step S2, the lithium source is selected from at least one of lithium carbonate, lithium chloride, lithium hydroxide and lithium fluoride; in step S2, the fluorine source is selected from lithium fluoride and / or ammonium fluoride; Preferably, in step S2, the phosphorus source is selected from at least one of phytic acid, phosphoric acid, lithium dihydrogen phosphate and ammonium phosphate; Preferably, in step S2, the transition metal salt is selected from at least one of acetate or nitrate of cobalt, acetate or nitrate of copper, acetate or nitrate of lanthanum, and acetate or nitrate of aluminum.
6. The method for preparing the surface-modified high-voltage lithium cobalt oxide positive electrode material according to claim 3, characterized in that: In step S1, the lithium cobalt oxide is a product of mixing cobalt trioxide and lithium carbonate, heating II in an air medium, and keeping II; The atomic molar ratio of the cobalt oxide to the lithium carbonate is 1:1 to 1.1; the temperature of the heating II is 600 to 1000° C.; the time of the heat preservation II is 2 to 6 hours; Wherein, the atomic mole number of the cobalt tetroxide is calculated as the atomic mole number of cobalt; The atomic mole number of the lithium carbonate is calculated as the atomic mole number of lithium; Preferably, the cobalt oxide comprises flaky nano cobalt oxide powder and spherical nano cobalt oxide powder; wherein, The preparation method of the flaky nano cobalt oxide powder comprises: heating cobalt salt and ammonia water at 60-100° C., keeping the temperature for 1-24 hours, and centrifugally drying to obtain nano cobalt hydroxide powder; heating the nano cobalt hydroxide powder in an air medium for III and keeping the temperature for III to obtain a product; wherein the heating temperature for III is 600-1000° C., and the keeping temperature for III is 2-6 hours; The preparation method of the spherical nano-cobalt trioxide powder comprises: a cobalt salt and sodium acetate are subjected to a hydrothermal reaction for 5 to 48 hours under a closed condition at 100 to 250° C., and the reaction liquid is separated and dried to obtain a product, wherein the drying temperature is 40 to 100° C.; The cobalt salt in the preparation process of cobalt tetroxide is selected from at least one of cobalt acetate, cobalt sulfate, cobalt nitrate and cobalt chloride; Preferably, in step S3, the heating rate of heating I is 5 to 20°C / min; the heating rate of heating II is 5 to 20°C / min; and the heating rate of heating III is 5 to 20°C / min.
7. A lithium cobalt oxide positive electrode component, comprising a conductive substrate and a slurry coated on the surface of the conductive substrate; characterized in that: The raw material of the slurry includes the surface-modified lithium cobalt oxide material according to any one of claims 1 to 3.
8. A high-voltage fast-charge lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte; characterized in that: The positive electrode component is the lithium cobalt oxide positive electrode component as claimed in claim 7.
9. A high-voltage fast-charge lithium-ion battery according to claim 8, characterized in that: The negative electrode is a metal lithium sheet, the separator is a Celgard2400 membrane, the electrolyte is a LB-372 high-voltage electrolyte; and the battery is a CR2016 button battery.
10. Use of the surface-modified lithium cobalt oxide material according to any one of claims 1 to 3 in a high-voltage ultra-fast charging lithium-ion battery.
Citation Information
Patent Citations
Lithium-ion secondary battery and positive electrode active material thereof
CN102569775A
Surface modified anode material for lithium ion battery and method
CN103633312A
Fluorophosphate lithium ion-electron mixed conductor modified lithium cobaltate composite material and preparation method thereof
CN106920947A
Coating modification method for reducing metal dissolution of high-voltage ternary positive electrode material
CN112018378A
Fluorinated lithium aluminum phosphate coated positive electrode material and preparation method thereof
CN114899376A
Cited By
Gradient-coated graphite composite negative electrode material, preparation method thereof and lithium ion battery
CN120565651A